Leber Hereditary Optic Neuropathy Gene Therapy: Adverse Events and Visual Acuity Results of All Patient Groups - Lam, Byron L.; Feuer, William J.; Davis, Janet L.; Porciatti, Vittorio; Yu, Hong; Levy, Robert B.; Vanner, Elizabeth; Guy, John (American journal of ophthalmology, 2022)
To assess safety of gene therapy in G11778A Leber hereditary optic neuropathy (LHON). Phase 1 clinical trial. Setting: single institution. Participants: Patients with G11778A LHON and chronic bilateral visual loss >12 months (group 1, n = 11), acute bilateral visual loss <12 months (group 2, n = 9), or unilateral visual loss (group 3, n = 8). Intervention: unilateral intravitreal AAV2(Y444,500,730F)-P1ND4v2 injection with low, medium, high, and higher doses to worse eye for groups 1 and 2 and better eye for group 3. Outcome Measures: Best-corrected visual acuity (BCVA), adverse events, and vector antibody responses. Mean follow-up was 24 months (range, 12-36 months); BCVAs were compared with a published prospective natural history cohort with designated surrogate study and fellow eyes. Incident uveitis (8 of 28, 29%), the only vector-related adverse event, resulted in no attributable vision sequelae and was related to vector dose: 5 of 7 (71%) higher-dose eyes vs 3 of 21 (14%) low-, medium-, or high-dose eyes (P < .001). Incident uveitis requiring treatment was associated with increased serum AAV2 neutralizing antibody titers (p=0.007) but not serum AAV2 polymerase chain reaction. Improvements of ≥15-letter BCVA occurred in some treated and fellow eyes of groups 1 and 2 and some surrogate study and fellow eyes of natural history subjects. All study eyes (BCVA ≥20/40) in group 3 lost ≥15 letters within the first year despite treatment. G11778A LHON gene therapy has a favorable safety profile. Our results suggest that if there is an efficacy effect, it is likely small and not dose related. Demonstration of efficacy requires randomization of patients to a group not receiving vector in either eye.